Rethinking our Notions of Asia - EAA Editorial Office (Education About Asia, 2021)
Fifteen years ago, we published a special section titled “Rethinking our Notions of Asia.” This column will hopefully help EAA readers and their students continue this process in multiple ways. Most fundamentally, students should first learn basic information about Asian cultures. That said, instructors and students in middle school, high school, and undergraduate classes can learn even more about Asia and the world through considering the essays below.
Keywords: Asia General; China; Culture; Education; History; International Relations; Japan; Korea; Sociology; Vietnam